Comparative Analysis of Heat Release, Bound Water Content and Compressive Strength of Alkali-Activated Slag-Fly Ash - Joseph, Shiju; Cizer, Özlem (Frontiers in Materials, 2022)
Optimizing the mix composition of alkali-activated materials is sometimes overwhelming due to the higher number of potential parameters that could be varied compared to designing a mix based on Portland cement. The present work focuses on understanding the correlations between compressive strength, bound water content, and heat release from the calorimeter. Different slag and fly ash proportions are studied at two different solution-to-binder (S/B) ratios. Alkali solutions are made with 5 M NaOH and water glass to have a final silica modulus of 1.28. Results indicate that, at similar S/B ratios, mixes with high amounts of slag develop high compressive strength corresponding to high bound water contents until 28 days and high heat release until 7 days. A good correlation exists between compressive strength with cumulative heat release and bound water content when the water-to-solid ratio of the initial mixture is also considered. These findings promise a less tedious method that could be employed to optimize the process for the mix design of alkali-activated materials.